CRISIS SITUATIONS MONITORING MODEL DEVELOPING ON THE BASE OF GEOINFORMATION TECHNOLOGIES USING - Lisitsin, V. Е.; Bielai, S. V.; Vorobyov, S. О.; Lugovskyi, І. S. (Honor and Law, 2019)
The relevance of conducting a study on improving the monitoring of crisis situations in modern society is proved. The analysis of the possibilities of geoinformation technologies for monitoring of crisis situations is carried out. To monitor the socio-economic and socio-political protest activity of the population, the “Analytics” model was created. The additional possibilities of the geoinformation system “Instrument” for improving the technology of digital map data analysis are shown. A corresponding set of software modules has been developed.